The Role and Utilization of CNN in Automatic Logo Based Document Image Retrieval Methods - K, Raveendra; Vinoth Kanna, R (International Journal of Engineering and Technology, 2018)
Automatic logo based document image retrieval process is an essential and mostly used method in the feature extraction applications. In this paper the architecture of Convolutional Neural Network (CNN) was elaborately explained with pictorial representations in order to understand the complex Convolutional Neural Networks process in a simplified way. The main objective of this paper is to effectively utilize the CNN in the process of automatic logo based document image retrieval methods.Â Â